Legal Aspects of Regulating Lobbying in the United States of America and Canada - E. A. Kremyanskaya (Vestnik MGIMO-Universiteta)
The author reviews history and peculiarities of the legal regulations of lobbying in USA and Canada, points out the tendencies of the legislation development. USA and Canada are among the first countries, which included legal regulations on the lobbying relations in the state government. The author explores the evolution of development of the lobbying legislation in the USA, and in particular reviews the Foreign Agents Registration Act of 1938, Federal Regulation of Lobbying Act of 1976, Lobbying Disclosure Act of 1995, as well as evolution of the Canadian legislation, where the Act on Lobbying of 1989 is in force, which had substantial changes during the last ten years. Taking into consideration the territorial form of state, the author reviews not only the federal legislation, but also laws on the level of states and provinces of these federations. Besides, the author covers the activity of the control bodies, order of registration and reporting by lobbyists of their professional activity, reveals pro and cons of the legal regulations of such institution as lobbying. In the article there is the list of information, which should be provided by lobbyists to the control bodies and the author correctly mentions that this list in USA is much wider, comparing to Canadian regulations. In the article the author reviews the liability for violations of lobbying legislation. In particular, in the USA the criminal liability is applied up to 5 years of imprisonment and financial penalties up to 200 thousand US dollars. Based on the USA and Canada experience the author reveals the key issues, which should be fixed by the legal regulations in the country and in particular: the clear definition of the lobbying and lobbyist, necessity of disclosure on the information about client and amounts paid, fixing in the control mechanisms and liability.